Avaliação da capacidade para o trabalho: análise frente ao envelhecimento funcional de servidores públicos em um município da região sul - Linhares, João Eduardo (2017)
This dissertation presents a conceptual approach about the evaluation of the work ability by focusing on the working population aging. The dissertation was developed with the objective of evaluating the factors associated with the work ability and the functional aging of public employees in a small municipality in the southern region of Brazil. The structure used was the dissertation model of articles compilation, comprising two articles. The study allowed to identify and to discuss the factors that influence positively or negatively the individual's work ability, which made it possible to construct a diagnosis and propose a future actions plan to promote the work ability. In article 1 of the dissertation, the systematic review of the literature on the Work Ability and Functional Aging was elaborated from the PROKNOW-C method, which resulted in a portfolio of articles aligned to the research theme. This portfolio was evaluated in a systemic way, through the application of conceptual lenses, highlighting strengths and weaknesses in each lens. This analysis provided the researcher with the necessary reference base for the research, especially with regard to the results of research and methodology, which were carried out with professionals of similar activities to public employees. In article 2, the servers participating in the research were classified and characterized according to their personal, work and social activities, which were considered independent variables in the study. Afterwards, it was determined the Work Ability Index - WAI, as a dependent variable, and the associated variables were positively or negatively identified, in order to evaluate the existence of an early functional aging. The data revealed a decline in the ability to work with advancing age, and that there is a share of workers with inadequate WAI under the age of 35, which pointed to a possible stage of early functional aging. The literature on the subject points out that it is possible to promote the work ability with measures capable of restoring the productive force of the worker. Thus, the present study demonstrated the importance of evaluating the work ability and functional aging, highlighting the main factors of influence, and the opportunities to improve the work ability of municipal public employees.